A study of diffuse radio sources and X-ray emission in six massive clusters - Parekh, V.; Dwarakanath, K.; Kale, R.; Intema, Hubertus (Oxford University Press, 2017)
The goal of this study is to extend our current knowledge of the diffuse radio source (halo and relic) populations to z > 0.3. Here, we report GMRT and EVLA radio observations of six galaxy clusters taken from the MAssive Cluster Survey (MACS) catalogue to detect diffuse radio emission. We used archival GMRT (150, 235, and 610 MHz) and EVLA (L band) data and made images at multiple radio frequencies of the following six clusters – MACSJ0417.5−1154, MACSJ1131.8−1955, MACSJ0308.9+2645, MACSJ2243.3−0935, MACSJ2228.5+2036, and MACSJ0358.8−2955. We detect diffuse radio emission (halo or relic, or both) in the first four clusters. In the last two clusters, we do not detect any diffuse radio emission but we put stringent upper limits on their radio powers. We also use archival Chandra X-ray data to carry out morphology and substructure analysis of these clusters. We find that based on X-ray data, these MACS clusters are non-relaxed and show substructures in their temperature distribution. The radio powers of the first four MACS clusters are consistent with their expected values in the LX–P1.4 GHz plot. However, we found ultrasteep spectrum radio halo in the MACSJ0417.5−1154 cluster whose rest-frame cut-off frequency is at ∼900 MHz. The remaining two clusters whose radio powers are ∼11 times below the expected values are most likely to be in the ‘off-state’ as has been postulated in some of the models of radio halo formation.